The sleep parameters of Olympic athletes: Characteristics and assessment instruments - de Mello, M. T.; Stieler, E.; Grade, I.; Filho, A. F. C.; Mendes, G.; Ituassu, N.; Silva, A. (International Journal of Sports Medicine, 2024)
This systematic review aims to identify the sleep parameters of Olympic athletes and the instruments used to assess and monitor the sleep of these athletes. The search was conducted until February 2023 and was performed in PubMed, Web of Science, and Scopus databases. This systematic review has included studies that investigated at least one of the following sleep parameters: total sleep time (TST), sleep onset latency (SOL), sleep efficiency (SE), awakenings after sleep onset (WASO), quality of sleep, daytime sleepiness, and chronotype; the participants were Olympic athletes. The search returned a total of 280 studies. After screening based on exclusion and inclusion criteria, 11 studies were included. The main results demonstrate that Olympic athletes have TST of 06:10 h, SE of 84%, SOL of 28 min, and WASO of 49 min. The most predominant chronotype is indifferent; over half of the athletes have poor sleep quality and complaints. Furthermore, actigraphy was the most used method to assess sleep. It is concluded that Olympic athletes have TST, SE, and WASO poor than the recommended values. In addition, sleep complaints and poor sleep quality were also observed. Among the objective sleep assessment methods, actigraphy was the method most frequently used in this population.